2021
DOI: 10.1016/j.image.2021.116359
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 discrimination framework for X-ray images by considering radiomics, selective information, feature ranking, and a novel hybrid classifier

Abstract: In medical imaging procedures for the detection of coronavirus, apart from medical tests, approval of diagnosis has special significance. Imaging procedures are also useful for detecting the damage caused by COVID-19. Chest X-ray imaging is frequently used to diagnose COVID-19 and different pneumonias. This paper presents a task-specific framework to detect coronavirus in X-ray images. Binary classification of three different labels (healthy, bacterial pneumonia, and COVID-19) was performed on two differentiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…First-order statistics (FOS) are generated using the histogram-based intensity analyses of an image. Concerning the histogram evaluations, six phenomena (mean, standard deviation, skewness, kurtosis, energy, and entropy) constitute the most preferred FOS features in the literature [14][15][16][17].…”
Section: First-order Statisticsmentioning
confidence: 99%
See 2 more Smart Citations
“…First-order statistics (FOS) are generated using the histogram-based intensity analyses of an image. Concerning the histogram evaluations, six phenomena (mean, standard deviation, skewness, kurtosis, energy, and entropy) constitute the most preferred FOS features in the literature [14][15][16][17].…”
Section: First-order Statisticsmentioning
confidence: 99%
“…Then, a discrete intensity value 'i' or the output of the function f (x,y) can own values in the range of [0, G − 1] which shows the values of intensity levels. Hereupon, the histogram arises as a statistical assessment of the repetition number of intensity levels among the image [14][15][16][17].…”
Section: First-order Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study proposes a novel hybrid classifier, using Gauss---map---based chaotic particle swarm optimization Neural network [40], which was designed to classify Coro--navirus, normal, and bacterial pneumonia X---ray images. The results showed 99.25% ac--curacy and 99.53% AUC metrics.…”
Section: Related Workmentioning
confidence: 99%
“…Rezaeijo et al7 based on the study of 9 feature selection procedures and 10 ML classifiers, it is shown that the ML model based on recursive feature elimination (RFE) and k-nearest neighborhood (KNN) classifier has the best performance in distinguishing confirmed and suspected patients with COVID-19 infection. When establishing the COVID-19 diagnosis model, we not only need to consider image quality, image sample quantity, and different data inputs, but also need to choose appropriate feature selection and prediction methods according to the actual situation to achieve the model optimization8 .…”
mentioning
confidence: 99%